Ownership structures and dividend policy: evidence from listed plantation companies in Malaysia / Sami RM Musallam and Coral Choo Pei Lin - RM Musallam, Sami; Choo, Coral Pei Lin (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
This research analyzed the relationship of ownership structures with dividend policy using a sample of 43 plantation companies listed on Bursa Malaysia from 2013 to 2015. The results of the Ordinary Least Square (OLS)analysis find that foreign ownership has a positive and significant influence on dividend policy while state ownership has a negative and significant influence on dividend policy. Furthermore, it was also found that Government Linked Investment Companies (GLICs) ownership has an insignificant influence on dividend policy. This study provides evidence to policymakers of government through their GLICs and states in selecting and deciding their dividend policies. Furthermore, it also provides evidence to shareholders and managers that companies with foreign ownership pay higher dividends while companies with state ownership pay lower dividends. This study is among the early studies that contributes to the finance and corporate governance literature by examining the relationship between GLICs as whole and foreign ownerships with a dividend policy in Malaysia.